2019
DOI: 10.1016/j.watres.2019.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise pH control to promote synergy of chemical and biological processes for augmenting short-chain fatty acid production from anaerobic sludge fermentation

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication 1 Stepwise pH control to promote synergy of chemical and biological processes for augmenting short-chain fatty acid production from anaerobic sludge fermentation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…In addition, damaged bacterial cells by hot wood ash extract (60-70 • C, pH 10.8-11.5) may be produced at the beginning of the fermentation. In addition, dead bacterial cells resulting from the initial treatment may be candidate substrates for obligate anaerobes (i.e., Proteinivoraceae and Tissierellaceae) as the taxa related to obligate anaerobes are known as sludge decomposers (Maspolim et al, 2015;Wang et al, 2019). The dead or weakened bacterial cell components may also be derived from transitional changes in the predominant bacteria, especially in the decrease in ORP at the early fermentation stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, damaged bacterial cells by hot wood ash extract (60-70 • C, pH 10.8-11.5) may be produced at the beginning of the fermentation. In addition, dead bacterial cells resulting from the initial treatment may be candidate substrates for obligate anaerobes (i.e., Proteinivoraceae and Tissierellaceae) as the taxa related to obligate anaerobes are known as sludge decomposers (Maspolim et al, 2015;Wang et al, 2019). The dead or weakened bacterial cell components may also be derived from transitional changes in the predominant bacteria, especially in the decrease in ORP at the early fermentation stage.…”
Section: Discussionmentioning
confidence: 99%
“…The dead or weakened bacterial cell components may also be derived from transitional changes in the predominant bacteria, especially in the decrease in ORP at the early fermentation stage. The decomposition of dead bacterial cells would be promoted chemically under high alkaline conditions (Wang et al, 2019). In the later phase, after the amount of substrates decreased, the second major substrates for the bacteria were wheat bran, which was added to the fermentation fluids at days 22 and 35 in Batches 1 and 3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The research performed by Zhou et al (2016) involved photometric analysis showed that the supernatant and membrane foulants in a submerged anaerobic membrane bioreactor (SAnMBR) were dominated by 90% of the total proteins and polysaccharides. At alkaline condition, the rate of initial hydrolysis of organic components is higher compared to the rates in neutral to acidic pH condition (Wang et al, 2019). The result of a high rate in initial hydrolysis can be a potential reason to increase the soluble proteins and carbohydrates in the reactor and finally accelerate the membrane fouling process (Li et al, 2019b).…”
Section: Membrane Fouling At Different Levels Of Phmentioning
confidence: 99%
“…Proteobacteria, Bacteroidetes, and Firmicutes dominated in FCS community (Fig 6A). The high abundance of Firmicutes (40.9% and 20.5% in spring and summer, respectively) in FCS might be attributed to the high level of organic pollution and low DO (Fig 2) as members in Firmicutes have been known for fermenting organic matters anaerobically and producing volatile organic acids [31,32]. The predominant taxa in FCS community, such as Novosphingobium, Acinetobacter, Flavobacterium, Geobacter, and Dechloromonas were also identified in other heavily polluted urban river sediments and anaerobic active sludge (Fig 6C) [31,33].…”
Section: Plos Onementioning
confidence: 99%
“…Compared with LHS, fermentation and sulfate reduction bacteria existed in high abundance in FCS (Fig 7), which might be explained by the niche selection and adaptation of such functional bacteria to the environment of high carbon and low DO content (Figs 1 and 2). The fermentative process is not effective for mineralization of organics, and the production of fermentation, such as short-chain fatty acids would contribute to the stench odor of urban river [31]. The production of FeS, H 2 S, organic sulfides, NH 3 , amines, and short chain fatty acids through sulfate reduction and fermentation was considered as the main cause of the black and stench of urban rivers [8].…”
Section: Difference Of Bacterial Communities In An Urban Center and Smentioning
confidence: 99%